Biomaterial Science : Anatomy and Physiology Aspects - Aguilar, Ludwig Erik (De Gruyter Textbook, 2022)
This book bridges the gap between a clinician's and material scientists' knowledge by elucidating upon the different biomaterials used in anatomical systems and how those materials react to the human body. It explores both established and future prospective of biomaterial types/designs, and considerations in material selection and synthesis, to guide students from non-clinical background in understanding the relations of material science and the human body.